Gene transfer into respiratory epithelial cells by targeting the polymeric immunoglobulin receptor. - Ferkol, T (1993)
A system for targeting foreign DNA to epithelial cells in vitro has been developed by exploiting receptor-mediated endocytosis. The polymeric immunoglobulin receptor transports dimeric immunoglobulin A and immunoglobulin M through epithelial cells, including those of the respiratory tract, by binding the immunoglobulins at the basolateral surface and transporting them across the cell. Fab fragments of antibodies directed against the extracellular portion of the receptor, secretory component, are similarly transported. Anti-human secretory component Fab fragments were covalently linked to a polycation, and complexed to various expression plasmids. When bound to an expression plasmid containing the Escherichia coli lacZ gene ligated to the Rous sarcoma virus promoter, the complexes transfected HT29.74 human colon carcinoma cells induced to express polymeric immunoglobulin receptor, but not those lacking the receptor. Primary cultures of human tracheal epithelial cells grown on collagen gels, which induce the expression of polymeric immunoglobulin receptor, were also transfected with the complexes. From 5 to 66% of the respiratory epithelial cells had beta-galactosidase activity after treatment, comparable to the percentage of cultured human tracheal epithelial cells that express polymeric immunoglobulin receptor (8-35%). The addition of excess human secretory component (Fab ligand) to the culture medium at the time of transfection blocked the delivery of DNA. The expression plasmid, either alone, complexed to the polycation, or complexed to a carrier based on an irrelevant Fab fragment, was not effective in transfecting either cell type. This DNA carrier system introduces DNA specifically into epithelial cells that contain pIgR in vitro.